A secondary battery, an electric device, a positive electrode active material, and a method for producing the same
Patent Information
- Application Number
- CN202510442515.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0038] In the technical solution of this application embodiment, the method uses a combination of one-time sintering, wet shaping, and spray drying granulation. The one-time sintering allows the lattice water in the raw materials and the gas generated during the formation of sodium iron pyrophosphate active materials to be released in advance. Then, wet shaping is used to eliminate the pore structure generated by the release of lattice water and gas during the one-time sintering process. Finally, spray drying granulation is used to make the prepared sodium iron pyrophosphate active materials have high sphericity. Ultimately, the sodium iron pyrophosphate active material particles have high sphericity and fewer and smaller pore structures, resulting in a secondary battery with high energy density.
Smart Images

Figure CN122930901A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and more specifically, to a secondary battery, an electrical device, a positive electrode active material, and a method for preparing the same. Background Technology
[0002] Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7)-type active materials possess advantages such as low cost, environmental friendliness, high theoretical capacity (129 mAh / g), and high average operating voltage (3.1 vs. Na). + With its characteristics such as low sodium content (Na) and low volume expansion (<4%), it is considered the most promising cathode material for sodium-ion batteries. Summary of the Invention
[0003] Without any theoretical constraints, the high sphericity Na4Fe3(PO4)2P2O7 particles prepared by the solid-state method generally have a large number of pores due to the decomposition and release of water of crystallization during the sintering process of the raw materials. This leads to the destruction of their sphericity and consequently, the low energy density of the resulting secondary battery.
[0004] In view of the above problems, this application provides a secondary battery, an electrical device, a positive electrode active material and a method for preparing the same, wherein the sodium iron pyrophosphate-based active material particles with high sphericity have fewer and smaller pore structures, resulting in a secondary battery with high energy density.
[0005] In a first aspect, this application provides a secondary battery, the secondary battery comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on at least a portion of the surface of the positive current collector, the positive active material layer comprising a positive active material, the positive active material comprising a sodium iron pyrophosphate-based active material, the sphericity of the sodium iron pyrophosphate-based active material being not less than 0.8, and the total pore volume of the sodium iron pyrophosphate-based active material being not greater than 0.013 cm³. 3 / g.
[0006] In the technical solution of this application embodiment, by making the sodium iron pyrophosphate active material particles with higher sphericity have less pore structure, the secondary battery has a higher energy density.
[0007] In some embodiments, the average pore size of the sodium iron pyrophosphate active material is no greater than 3 nm.
[0008] In the above implementation process, by controlling the high sphericity of the sodium iron pyrophosphate active material particles to have a small pore structure, the secondary battery can have a high energy density.
[0009] In some embodiments, the sphericity of the sodium iron pyrophosphate active material is 0.82 to 0.85.
[0010] In the above-mentioned process, the higher the sphericity of the sodium iron pyrophosphate active material, the better it is for the compaction density of the formed positive electrode sheet. By controlling the sphericity of the sodium iron pyrophosphate active material to be 0.82–0.85, the formed positive electrode sheet can have a higher compaction density.
[0011] In some embodiments, the total pore volume of the sodium iron pyrophosphate-based active material is 0.011 cm³. 3 / g~0.013cm 3 / g; and / or
[0012] The average pore size of the sodium iron pyrophosphate active material is 2.5 nm to 3 nm; and / or
[0013] The median particle size Dv50 of the sodium iron pyrophosphate active material is 0.1 μm to 0.3 μm; and / or
[0014] The specific surface area of the sodium iron pyrophosphate active material is 5.5 m². 2 / g~5.7m 2 / g; and / or
[0015] The compacted density of the sodium iron pyrophosphate active material is 1.90 g / cm³. 3 ~2.10g / cm 3 ; and / or
[0016] The 3T compaction density of the sodium iron pyrophosphate active material is 2.10 g / cm³. 3 ~2.3g / cm 3 .
[0017] In some embodiments, the compaction density of the positive electrode sheet is 2.1 g / cm³. 3 ~2.2g / cm 3 .
[0018] Secondly, this application provides an electrical device, which includes the secondary battery provided in the first aspect.
[0019] Thirdly, this application provides a positive electrode active material, which includes a sodium iron pyrophosphate active material, wherein the sphericity of the sodium iron pyrophosphate active material is not less than 0.8, and the total pore volume of the sodium iron pyrophosphate active material is not greater than 0.013 cm³. 3 / g.
[0020] In the technical solution of this application embodiment, by making the sodium iron pyrophosphate active material particles with high sphericity have less pore structure, the resulting secondary battery has a high energy density.
[0021] In some embodiments, the average pore size of the sodium iron pyrophosphate active material is no greater than 3 nm.
[0022] In the above implementation process, by controlling the high sphericity of the sodium iron pyrophosphate active material particles to have a small pore structure, the secondary battery can have a high energy density.
[0023] In some embodiments, the sphericity of the sodium iron pyrophosphate active material is 0.82 to 0.85.
[0024] In the above-mentioned process, the higher the sphericity of the sodium iron pyrophosphate active material, the better it is for the compaction density of the formed positive electrode sheet. By controlling the sphericity of the sodium iron pyrophosphate active material to be 0.82–0.85, the formed positive electrode sheet can have a higher compaction density.
[0025] In some embodiments, the total pore volume of the sodium iron pyrophosphate-based active material is 0.011 cm³. 3 / g~0.013cm 3 / g; and / or
[0026] The average pore size of the sodium iron pyrophosphate active material is 2.5 nm to 3 nm; and / or
[0027] The particle size of the sodium iron pyrophosphate active material is 0.1 μm to 0.3 μm; and / or
[0028] The specific surface area of the sodium iron pyrophosphate active material is 5.5 m². 2 / g~5.7m 2 / g; and / or
[0029] The compacted density of the sodium iron pyrophosphate active material is 1.90 g / cm³. 3 ~2.10g / cm 3 ; and / or
[0030] The 3T compaction density of the sodium iron pyrophosphate active material is 2.10 g / cm³. 3 ~2.3g / cm 3
[0031] Fourthly, embodiments of this application provide a method for preparing a positive electrode active material, the method comprising:
[0032] The raw materials are formulated into a mixed slurry, wherein the raw materials include a sodium source, an iron source, and a phosphorus source;
[0033] The mixed slurry is granulated to obtain mixed particles;
[0034] The mixed particles are sintered once to obtain an intermediate, and the temperature of the first sintering is greater than 370°C.
[0035] The intermediate material is subjected to wet shaping to obtain a primary slurry.
[0036] The initial slurry is spray-dried and granulated to obtain initial granules;
[0037] The primary particles are then subjected to secondary sintering to obtain the positive electrode active material.
[0038] In the technical solution of this application embodiment, the method uses a combination of one-time sintering, wet shaping, and spray drying granulation. The one-time sintering allows the lattice water in the raw materials and the gas generated during the formation of sodium iron pyrophosphate active materials to be released in advance. Then, wet shaping is used to eliminate the pore structure generated by the release of lattice water and gas during the one-time sintering process. Finally, spray drying granulation is used to make the prepared sodium iron pyrophosphate active materials have high sphericity. Ultimately, the sodium iron pyrophosphate active material particles have high sphericity and fewer and smaller pore structures, resulting in a secondary battery with high energy density.
[0039] In some embodiments, the temperature of the first sintering is 420°C to 450°C; and / or
[0040] The sintering time for the first sintering is 5h to 15h; and / or
[0041] The secondary sintering temperature is 500℃~600℃; and / or
[0042] The secondary sintering time is 24h to 34h.
[0043] In the above implementation process, higher primary sintering temperatures and longer times facilitate the release of lattice water from the raw materials and gases generated during the formation of sodium iron pyrophosphate-based active materials. This reduces the possibility of pore structures caused by gases during secondary sintering. Conversely, lower primary sintering temperatures and shorter times reduce energy consumption, thus contributing to cost control. By controlling the primary sintering temperature to 420℃–450℃ and the time to 5h–15h, a balance can be struck between minimizing the pore structure of sodium iron pyrophosphate-based active materials and cost control. Similarly, higher secondary sintering temperatures and longer times promote the complete reaction of the raw materials into sodium iron pyrophosphate-based active materials. Lower secondary sintering temperatures and shorter times further reduce energy consumption, also contributing to cost control. By controlling the secondary sintering temperature to 500℃–600℃ and the time to 24h–34h, a balance can be struck between the yield and cost control of sodium iron pyrophosphate-based active materials.
[0044] In some embodiments, the difference between the median particle size Dv50 of the solid phase in the primary slurry and the median particle size Dv50 of the solid phase in the mixed slurry is not greater than 0.2 μm.
[0045] In the above implementation process, by controlling the difference between the median particle size Dv50 of the solid phase in the initial slurry and the median particle size Dv50 of the solid phase in the mixed slurry to be no greater than 0.2 μm, the pore structure in the intermediate is opened as completely as possible, which is beneficial to reduce and minimize the pore structure of the final sodium iron pyrophosphate active material.
[0046] In some embodiments, the solvent used in the wet forming process is an organic solvent.
[0047] In the above implementation process, by using organic solvents as solvents for wet forming, the possibility of generating impurity phases such as NaFePO4 in sodium iron pyrophosphate active materials can be reduced, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial to improving the specific capacity of sodium iron pyrophosphate active materials.
[0048] In some embodiments, the organic solvent includes alcohol solvents; and / or
[0049] The inlet air temperature of the spray drying granulation is 180℃~250℃, and the outlet air temperature of the spray drying granulation is 85℃~95℃.
[0050] In the above implementation process, by using alcohol solvents as the solvent for wet forming, alcohol solvents usually have a low boiling point, which can reduce the temperature of subsequent spray drying granulation, thereby reducing energy consumption and helping to control costs.
[0051] In some embodiments, the iron source includes at least one of ferric phosphate, ferric acetylacetone, ferrous oxalate, ferric acetate, ferric citrate, or ferrous citrate.
[0052] In the above implementation process, the combined use of one-time sintering, wet shaping and spray drying granulation is more conducive to improving the compaction density of sodium iron pyrophosphate active materials prepared from organic iron sources such as iron phosphate, iron acetylacetone, ferrous oxalate, iron acetate, iron citrate or ferrous citrate. Attached Figure Description
[0053] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0054] Figure 1 This application provides structural schematic diagrams of vehicles for some embodiments;
[0055] Figure 2 This is an exploded structural diagram of a secondary battery provided in some embodiments of this application;
[0056] Figure 3 This is a schematic diagram of the structure of a battery cell provided in some embodiments of this application;
[0057] Figure 4 Exploded views of a single battery cell provided in some embodiments of this application;
[0058] Figure 5 This is a first structural schematic diagram of the positive electrode sheet provided in some embodiments of this application;
[0059] Figure 6 This is a schematic diagram of the second structure of the positive electrode sheet provided in some embodiments of this application;
[0060] Figure 7 Flowcharts illustrating methods for preparing positive electrode active materials provided in some embodiments of this application;
[0061] Figure 8 A flowchart illustrating the fabrication process of a secondary battery provided in some embodiments of this application;
[0062] Figure 9 Scanning electron microscope images of the intermediate provided in Embodiment 1 of this application (magnifications of 1K (top) and 3K (bottom));
[0063] Figure 10 Scanning electron microscope images of the intermediate provided in Embodiment 2 of this application (magnifications of 1K (top) and 3K (bottom));
[0064] Figure 11 Scanning electron microscope images of the intermediate provided in Comparative Example 1 of this application (magnifications of 1K (top) and 3K (bottom));
[0065] Figure 12 Scanning electron microscope images of the intermediate provided in Comparative Example 2 of this application (magnifications of 1K (top) and 3K (bottom));
[0066] Figure 13 Scanning electron microscope images of the intermediate provided in Comparative Example 3 of this application (magnifications of 1K (top) and 3K (bottom));
[0067] Figure 14 This is a scanning electron microscope image of the sodium iron pyrophosphate active material provided in Example 1 of this application;
[0068] Figure 15 This is a scanning electron microscope image of the sodium iron pyrophosphate active material provided in Comparative Example 4 of this application;
[0069] Figure 16 This is a scanning electron microscope image of the sodium iron pyrophosphate active material provided in Comparative Example 5 of this application.
[0070] The reference numerals in the detailed embodiments are as follows:
[0071] 1000 - Vehicle; 100 - Secondary battery; 200 - Motor; 300 - Controller; 10 - Housing; 11 - Accommodation space; 12 - First part; 13 - Second part; 20 - Battery cell; 21 - Shell; 211 - Opening; 22 - End cap assembly; 221 - End cap; 222 - Electrode terminal; 23 - Electrode assembly; 231 - Positive electrode sheet; 2311 - Positive current collector; 2312 - Positive active material layer; 24 - Current collector component; 25 - Insulation protection component. Detailed Implementation
[0072] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0073] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0074] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0075] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0076] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0077] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple groups" refers to two or more (including two groups), and "multiple pieces" refers to two or more (including two pieces).
[0078] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0079] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0080] Currently, judging from market trends, the application of power batteries is becoming increasingly widespread. Power batteries are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively used in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace. With the continuous expansion of power battery applications, market demand is also constantly increasing.
[0081] Sodium-ion batteries can be used as power batteries. Sodium is abundant, which can significantly reduce battery costs, thus giving sodium-ion batteries broad application prospects. For example, sodium-ion batteries can be used in portable electronic devices, electric vehicles, and other fields. Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7) type positive electrode active materials have advantages such as low cost, environmental friendliness, high theoretical capacity (129mAh / g), and high average operating voltage (3.1Vs.Na2O7). + With its characteristics such as low volume expansion (less than 4%), sodium-ion battery cathode material is considered to be the most promising.
[0082] Without any theoretical constraints, the high sphericity Na4Fe3(PO4)2P2O7 particles prepared by the solid-state method currently have a large number of pores due to the decomposition of raw materials (such as organic iron sources) and the release of crystal water gas during the sintering process. This results in the destruction of their sphericity and consequently, a lower energy density in the resulting secondary battery.
[0083] Based on the above considerations, in order to improve the pore structure of high-sphericity sodium iron pyrophosphate active material particles and thus improve the energy density of the formed secondary battery, this application proposes a secondary battery. The secondary battery includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least a portion of the surface of the positive current collector. The positive active material layer includes a positive active material, which is a sodium iron pyrophosphate active material. The sphericity of the sodium iron pyrophosphate active material is greater than or equal to 0.8, and the total pore volume of the sodium iron pyrophosphate active material is not greater than 0.013 cm³. 3 / g.
[0084] In such secondary batteries, by making the active material particles of sodium iron pyrophosphate with high sphericity have less pore structure, the secondary battery has a high energy density.
[0085] This secondary battery can be used, but is not limited to, in electrical devices such as vehicles, ships, or aircraft. A power system for such an electrical device can be constructed using a secondary battery disclosed in this application.
[0086] This application provides an electrical device that uses a battery as a power source. The electrical device can be, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0087] For ease of explanation, the following embodiments will be described using a vehicle 1000 as an example of an electrical device according to an embodiment of this application.
[0088] Please refer to Figure 1 , Figure 1 This is a schematic diagram of the structure of a vehicle 1000 provided in some embodiments of this application. The vehicle 1000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A secondary battery 100 is installed inside the vehicle 1000, and the secondary battery 100 can be located at the bottom, front, or rear of the vehicle 1000. The secondary battery 100 can be used to power the vehicle 1000; for example, the secondary battery 100 can serve as the operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200. The controller 300 is used to control the secondary battery 100 to supply power to the motor 200, for example, to meet the power needs of the vehicle 1000 during startup, navigation, and driving.
[0089] In some embodiments of this application, the secondary battery 100 can not only serve as the operating power source for the vehicle 1000, but also as the driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0090] In this application, the secondary battery 100 can refer to a single battery cell 20, or it can refer to a single physical module comprising multiple battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, battery module, etc. The secondary battery 100 may include a housing 10 for encapsulating multiple battery cells 20, and the housing 10 can prevent liquids or other foreign objects from affecting the charging or discharging of the battery cells 20.
[0091] Figure 2 This is an exploded structural diagram of a secondary battery provided in some embodiments of this application. Please refer to... Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20, with the battery cell 20 housed within the housing 10.
[0092] The housing 10 provides a receiving space 11 for the battery cell 20. In some embodiments, the housing 10 may include a first portion 12 and a second portion 13, which overlap each other to define the receiving space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 may be sealed by a sealant (not shown), such as a sealing ring, sealant, etc.
[0093] The first part 12 and the second part 13 can be of various shapes, such as cuboids, cylinders, etc. The first part 12 can be a hollow structure with an opening on one side to form a cavity for accommodating the battery cell 20, and the second part 13 can also be a hollow structure with an opening on one side to form a cavity for accommodating the battery cell 20. When the opening side of the second part 13 covers the opening side of the first part 12, a housing 10 with an accommodating space 11 is formed. Of course, as... Figure 2 As shown, the first part 12 can also be a hollow structure with an opening on one side, and the second part 13 can be a plate-like structure. The second part 13 covers the opening side of the first part 12, thus forming a box 10 with a accommodating space 11.
[0094] In the secondary battery 100, there are multiple battery cells 20. These multiple battery cells 20 can be connected in series, parallel, or in a mixed manner. A mixed connection means that multiple battery cells 20 are connected in both series and parallel. Multiple battery cells 20 can be directly connected in series, parallel, or in a mixed manner, and then the entire assembly of the multiple battery cells 20 is housed within the housing 10. Alternatively, multiple battery cells 20 can first be connected in series, parallel, or in a mixed manner to form a battery module, and then multiple battery modules can be connected in series, parallel, or in a mixed manner to form a whole, which is also housed within the housing 10. The battery cells 20 can be cylindrical, flat, cuboid, or other shapes. Figure 2 An example is shown where the battery cell 20 is square.
[0095] In some embodiments, the secondary battery 100 may further include a busbar (not shown), through which multiple battery cells 20 can be electrically connected to each other to achieve series, parallel, or mixed connection of multiple battery cells 20.
[0096] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of this application. Figure 4 Exploded views of a battery cell 20 provided for some embodiments of this application. Please refer to... Figure 3 and Figure 4 The battery cell 20 may include a housing 21, an end cap assembly 22, and an electrode assembly 23. The housing 21 has an opening 211, the electrode assembly 23 is housed within the housing 21, and the end cap assembly 22 is used to seal the opening 211.
[0097] The shape of the outer casing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a cuboid structure, the outer casing 21 can be a cuboid structure. Figure 3 and Figure 4 An example is shown where the housing 21 and electrode assembly 23 are square.
[0098] The outer shell 21 can also be made of various materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc. This application embodiment does not impose any special restrictions on this.
[0099] The end cap assembly 22 includes an end cap 221 and electrode terminals 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a sealed mounting space (not shown) for accommodating the electrode assembly 23. The mounting space also accommodates an electrolyte, such as an electrolyte solution. As a component that outputs electrical energy to the electrode assembly 23, the end cap assembly 22 has electrode terminals 222 for electrical connection to the electrode assembly 23, specifically, the electrode terminals 222 are electrically connected to the tabs of the electrode assembly 23. For example, the electrode terminals 222 and the tabs are connected via a current collector 24 to achieve the electrical connection between the electrode terminals 222 and the tabs.
[0100] It should be noted that the opening 211 of the outer casing 21 can be one or two. If the outer casing 21 has one opening 211, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22. The two electrode terminals 222 are used to electrically connect to the positive electrode tab and the negative electrode tab of the electrode assembly 23, respectively. If the outer casing 21 has two openings 211, for example, the two openings 211 are located on opposite sides of the outer casing 21, the end cap assembly 22 can also be two, and the two end cap assemblies 22 respectively cover the two openings 211 of the outer casing 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal 222, used to electrically connect to the positive electrode tab of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal 222, used to electrically connect to the negative electrode plate of the electrode assembly 23.
[0101] In some embodiments, such as Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the outer periphery of the electrode assembly 23. The insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is adhesive tape bonded to the outer periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 surrounds the outer periphery of multiple electrode assemblies 23, forming a single integral structure to maintain the structural stability of the electrode assembly 23.
[0102] The electrode assembly 23 includes a positive electrode 231, a negative electrode 231, and a separator. The separator is located between the positive electrode 231 and the negative electrode 231 and serves as a separator. The electrode assembly 23 can be a wound structure or a stacked structure, and the embodiments of this application are not limited to these.
[0103] This application does not impose any particular restrictions on the positive electrode 231, the negative electrode, and the separator.
[0104] In some embodiments, the separator can be a PP (polypropylene) porous membrane, a PE (polyethylene) porous membrane, a polyimide porous membrane, or a porous membrane formed by a composite of various polymers.
[0105] In some embodiments, the positive electrode 231 includes a positive current collector 2311 and a positive active material layer 2312 covering at least one surface of the positive current collector 2311 in the thickness direction; the positive current collector 2311 without the positive active material layer 2312 protrudes from the positive current collector 2311 with the positive active material layer 2312 coated, and the positive current collector 2311 without the positive active material layer 2312 coated serves as a positive electrode tab. The material of the positive electrode current collector 2311 may include aluminum foil, aluminum foam, aluminum composite current collector (with a polymer support layer in the middle, and aluminum metal layers on both surfaces of the support layer), nickel foil, nickel foam, etc.; the positive electrode active material layer 2312 may include, in addition to the aforementioned sodium iron pyrophosphate active materials, one or a mixture of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium olivine-structured lithium phosphates, such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, etc. Lithium iron phosphate, lithium manganese oxide, etc.; the binder in the positive electrode active material layer 2312 is selected from at least one of vinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid copolymer; the dispersant in the positive electrode active material layer 2312 is selected from polyvinylpyrrolidone, etc.; the conductive particles in the positive electrode active material layer 2312 are selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, activated carbon, graphite sheets, graphite particles, and mesophase carbon microspheres.
[0106] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet 231, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g. N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0107] In some embodiments, the negative electrode includes a negative current collector and a negative active material layer covering at least one surface of the negative current collector in the thickness direction; the negative current collector without the negative active material layer protrudes from the negative current collector with the negative active material layer, and the negative current collector without the negative active material layer serves as a negative electrode tab. The material of the negative current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, or a polymer substrate coated with a conductive metal, wherein the conductive metal includes, but is not limited to, copper, nickel, or titanium, and the polymer substrate material includes, but is not limited to, at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene terephthalate, and poly(p-phenylene terephthalate); the negative active material in the negative active material layer includes carbon materials, elemental lithium, and alloys formed by lithium and other metallic or non-metallic elements, wherein the carbon materials include, but are not limited to, at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon materials, all of which are commercially available. Metallic elements include tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In), and tin foil (Pt), while non-metallic elements include boron (B), carbon (C), and silicon (Si).
[0108] In other embodiments, the current collector of the negative electrode sheet may also include a current collector body and a base coating. The base coating may be disposed on at least one side of the current collector body. The base coating basically does not contain negative electrode active material, but may contain a small amount of carbon material. However, the carbon material forms a thin coating and cannot function as a negative electrode active material. In this embodiment, the negative electrode sheet can be an electrode sheet without a negative electrode active material layer. For a negative electrode sheet without a negative electrode active material layer, when the current collector of the negative electrode sheet does not contain a base coating, the film layer of the negative electrode sheet can be disposed on the surface of at least one side of the current collector body; when the current collector of the negative electrode sheet includes a base coating, the film layer of the negative electrode sheet can be disposed on the surface of the base coating away from the current collector body.
[0109] In some embodiments, the electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.
[0110] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0111] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0112] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0113] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0114] This application embodiment provides a secondary battery, the secondary battery including a positive electrode, such as 5 and Figure 6 Please refer to the structural diagrams of the positive electrode plates. Figure 5 and Figure 6 The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least a portion of the surface of the positive current collector. The positive active material layer includes a positive active material, which is a sodium iron pyrophosphate-based active material. The sphericity of the sodium iron pyrophosphate-based active material is not less than 0.8, and the total pore volume of the sodium iron pyrophosphate-based active material is not greater than 0.013 cm³. 3 / g.
[0115] Please continue reading. Figure 5 The positive electrode active material layer 2312 can be disposed on one side of the positive electrode current collector. Please refer to [further details]. Figure 6 The positive electrode active material layer 2312 can also be disposed on both sides of the positive electrode current collector. The material of the positive electrode current collector 2311 can be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0116] Sodium iron pyrophosphate active materials refer to modified or unmodified sodium iron pyrophosphate active materials. Modification includes doping or coating.
[0117] Sphericity measures the degree to which particles tend towards a spherical shape. The greater the sphericity, the more spherical the particles are. Sphericity can be determined by taking electron microscope (SEM) images of sodium iron pyrophosphate active materials, importing them into IPP software for segmentation, and calculating the ratio of the particle perimeter equivalent diameter to the particle area equivalent diameter using the software's calculation function. The average sphericity is then obtained as the sphericity of the sodium iron pyrophosphate active material.
[0118] The total pore volume of sodium iron pyrophosphate active materials is a term known in the art and can be determined using instruments and methods known in the art. An exemplary test method is as follows: A certain mass of a sodium iron pyrophosphate active material sample (e.g., 1.5 g to 3.5 g) is placed in a sample tube, dried, and then degassed at 200°C for 2 hours. The sample is then placed in a Tristar II 3020 instrument analysis station for testing to obtain the total pore volume of the sodium iron pyrophosphate active material. The adsorbed gas during the test can be nitrogen, and the adsorption temperature can be 77 K (K represents Kelvin temperature).
[0119] This secondary battery achieves a high energy density by using highly spherical sodium iron pyrophosphate active material particles with fewer pores.
[0120] In some embodiments of this application, the average pore size of the sodium iron pyrophosphate active material is no greater than 3 nm.
[0121] The average aperture can be obtained by analyzing high-resolution transmission electron microscopy. Representative areas of the magnified electron image are selected, the apertures of the through holes are counted, and the average aperture of more than 10 representative areas is taken to obtain the average aperture.
[0122] By controlling the sphericity of sodium iron pyrophosphate-based active material particles to have a smaller pore structure, the secondary battery can achieve a higher energy density.
[0123] In some embodiments of this application, the sphericity of the sodium iron pyrophosphate active material is 0.82–0.85. Higher sphericity of the sodium iron pyrophosphate active material is more conducive to the compaction density of the formed positive electrode sheet. By controlling the sphericity of the sodium iron pyrophosphate active material to 0.82–0.85, the formed positive electrode sheet can have a higher compaction density.
[0124] For example, the sphericity of sodium iron pyrophosphate active materials can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.9, etc., or any value within the range of not less than 0.8.
[0125] In some embodiments of this application, the total pore volume of the sodium iron pyrophosphate-based active material is 0.011 cm³. 3 / g~0.013cm 3 / g.
[0126] For example, the total pore volume of sodium iron pyrophosphate-based active materials can be 0.011 cm³. 3 / g, 0.0111cm 3 / g, 0.0112cm3 / g, 0.0113cm 3 / g, 0.0114cm 3 / g, 0.0115cm 3 / g, 0.0116cm 3 / g, 0.0117cm 3 / g, 0.0118cm 3 / g, 0.0119cm 3 / g, 0.012cm 3 / g, 0.0121cm 3 / g, 0.0122cm 3 / g, 0.0123cm 3 / g, 0.0124cm 3 / g, 0.0125cm 3 / g, 0.0126cm 3 / g, 0.0127cm 3 / g, 0.0128cm 3 / g, 0.0129cm 3 / g or 0.13cm 3 / g, etc., can also be 0.011cm. 3 / g~0.013cm 3 Any value within the range / g.
[0127] In some embodiments of this application, the average pore size of the sodium iron pyrophosphate active material is 2.5 nm to 3 nm.
[0128] For example, the average pore size of sodium iron pyrophosphate active materials can be 2.5nm, 2.55nm, 2.6nm, 2.65nm, 2.7nm, 2.75nm, 2.8nm, 2.85nm, 2.9nm, 2.95nm or 3nm, etc., or it can be any value in the range of 2.5nm to 3nm.
[0129] In some embodiments of this application, the median particle size Dv50 of the sodium iron pyrophosphate active material is 0.1 μm to 0.3 μm.
[0130] The median particle size Dv50 is the particle size corresponding to 50% of the cumulative amount in the volumetric particle size distribution map. The volumetric particle size distribution map, also known as the differential particle size distribution map, is a curve plotted with particle size on the x-axis and the differential distribution of particle size at different dimensions on the y-axis. It can accurately reflect the particle size distribution characteristics of a material. A laser particle size analyzer can be used to determine the volumetric particle size distribution of the material and plot the interval particle size distribution curve. When measuring the median particle size of the positive electrode active material in the active material layer of the electrode sheet, the positive electrode active material layer can be removed, immersed in the solvent NMP, and the binder in the positive electrode active material layer can be washed out to obtain the powder material of the positive electrode active material layer. After drying the powder material, it is detected using a Mastersizer3000 laser particle size analyzer to obtain the volumetric particle size distribution map. The median particle size of the positive electrode active material can be obtained from the peaks in the volumetric particle size distribution map.
[0131] Understandably, with sphericity and average pore size remaining constant, smaller particle size results in smaller gaps between particles, which is more conducive to increasing powder compaction density.
[0132] For example, the median particle size Dv50 of sodium iron pyrophosphate active materials can be 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.2 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm or 0.3 μm, etc., or it can be any value in the range of 0.1 μm to 0.3 μm.
[0133] In some embodiments of this application, the specific surface area of the sodium iron pyrophosphate active material is 5.5 m². 2 / g~5.7m 2 / g.
[0134] Specific surface area refers to the total surface area per unit mass of a substance. Specific surface area can be measured using instruments and methods known in the art, such as nitrogen adsorption specific surface area analysis and calculated using the BET method.
[0135] For example, the specific surface area of sodium iron pyrophosphate-based active materials can be 5.5 m². 2 / g, 5.52m 2 / g, 5.54m 2 / g, 5.56m 2 / g, 5.58m 2 / g, 5.6m 2 / g, 5.62m 2 / g, 5.64m 2 / g, 5.66m 2 / g, 5.68m 2 / g, 5.7m 2 / g, etc., can also be 5.5m. 2 / g~5.7m 2 Any value within the range / g.
[0136] It should be noted that the specific surface area and volumetric particle size distribution measurements are for secondary particles, which are aggregates of primary particles.
[0137] In some embodiments of this application, the compacted density of 1T of sodium iron pyrophosphate-based active material is 1.90 g / cm³. 3 ~2.10g / cm 3 .
[0138] 1T compaction density refers to the compaction density of powder under 1T pressure. Powder compaction density can be tested using a powder compaction density meter.
[0139] For example, the compacted density of 1T of sodium iron pyrophosphate-based active materials can be 1.90 g / cm³. 3 1.95g / cm 3 2.00g / cm 3 2.05g / cm 3 Or 2.10 g / cm 3 It can also be 1.90 g / cm³. 3 ~2.10g / cm 3 Any value within the range.
[0140] In some embodiments of this application, the 3T compaction density of the sodium iron pyrophosphate-based active material is 2.10 g / cm³. 3 ~2.3g / cm 3 .
[0141] 3T compaction density refers to the compaction density of powder under 3T pressure. Powder compaction density can be tested using a powder compaction density meter.
[0142] For example, the 3T compaction density of sodium iron pyrophosphate-based active materials can be 2.10 g / cm³. 3 2.15g / cm 3 2.20g / cm 3 2.25g / cm 3 Or 2.30 g / cm 3 It can also be 2.10 g / cm³. 3 ~2.3g / cm 3 Any value within the range.
[0143] In some embodiments of this application, the compaction density of the positive electrode sheet is 2.1 g / cm³. 3~2.2g / cm 3 .
[0144] Electrode compaction density testing can be performed by measuring the mass (g / cm³) of the positive electrode active material layer per unit area on one side. 2 The density of the positive electrode active material layer (PD) is determined by the thickness (cm) of the positive electrode active material layer on one side (number of sampling points > 14). Specifically, the compaction density PD of the positive electrode active material layer is equal to the mass of the positive electrode active material layer on one side per unit area (g / cm³). 2 ) / Thickness of the positive electrode active material layer (cm). (Under the calculated coating quality conditions, if the cold-pressed thickness reaches the design value and there are no processing problems such as demolding, it means that the compaction density can meet the standard.)
[0145] Because sodium iron pyrophosphate active materials have fewer and smaller pore structures, they are less prone to breakage. Therefore, they can withstand greater cold pressing pressure when preparing positive electrode sheets, resulting in higher compaction density of the positive electrode sheets.
[0146] For example, the compaction density of the positive electrode sheet can be 2.1 g / cm³. 3 2.11 g / cm 3 2.12 g / cm 3 2.13 g / cm 3 2.14 g / cm 3 2.15g / cm 3 2.16 g / cm 3 2.17 g / cm 3 2.18 g / cm 3 2.19 g / cm 3 Or 2.2g / cm 3 It can also be 2.1 g / cm³. 3 ~2.2g / cm 3 Any value within the range.
[0147] In some embodiments of this application, the energy density of the secondary battery is 276Wh / L to 280Wh / L.
[0148] For example, the energy density of the secondary battery can be 276Wh / L, 276.5Wh / L, 277Wh / L, 277.5Wh / L, 278Wh / L, 278.5Wh / L, 279Wh / L, 279.5Wh / L, or 280Wh / L, or any value within the range of 276Wh / L to 280Wh / L.
[0149] In some embodiments of this application, the active material of sodium iron pyrophosphate includes Na. x R y P m On Wherein, 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7<m≤4.2, 14.5≤n≤15.5, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Cr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, or Pb.
[0150] The content of each element can be obtained by inductively coupled plasma atomic emission spectrometry (ICP).
[0151] It should be noted that the above limitation on x includes the molar content of Na under different charge and discharge states of the battery (typically the battery voltage is between 2-5V).
[0152] Understandably, sodium (Na) is intercalated and deintercalated during the charging and discharging process of a battery. The Na content in the positive electrode varies depending on the state of discharge. The Na content can be measured using molar content, but is not limited to this. Simultaneously, when a positive electrode material is applied to the positive electrode in a battery system, the Na content in the positive electrode material typically changes after charge-discharge cycles. In the examples of positive electrode materials listed in this application, unless otherwise specified, the Na content refers to the initial state of the material. Regarding "Na content refers to the initial state of the material," the initial state of the material refers to its state before being added to the positive electrode slurry. It is understood that new materials obtained by appropriately modifying the listed positive electrode materials are also within the scope of positive electrode materials. The aforementioned appropriate modification refers to acceptable modification methods for the positive electrode material; non-limiting examples include coating modification.
[0153] It is understandable that the molar content of R, y, and the molar content of Na are similar, so we will not elaborate further here.
[0154] For example, Na x R y P m O n In this case, x can be 3.5, 3.55, 3.6, 3.65, 3.7, 3.75, 3.8, 3.85, 3.9, 3.95, 4, 4.05, 4.1, 4.15, 4.2, 4.25, 4.3, 4.35, 4.4, 4.45, or 4.5, or any value within the range of 3.5 to 4.5. Na x R y P m O n In this case, y can be 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, or 3.5, or any value within the range of 2.5 to 3.5. Na x R y Pm O n In this case, m can be 3.7, 3.75, 3.8, 3.85, 3.9, 3.91, 3.92, 3.93, 3.94, 3.94, 3.95, 3.96, 3.97, 3.98, 3.99, 4, 4.05, 4.1, 4.15, or 4.2, etc., or any value within the range of 3.7 to 4.2. Na x R y P m O n In this case, n can be 14.5, 14.6, 14.7, 14.8, 14.9, 15, 15.1, 15.2, 15.3, 15.4 or 15.5, etc., or any value in the range of 14.5 to 15.5.
[0155] In some embodiments of this application, y:x < 3:4. By controlling y:x < 3:4, the content of impurity phases such as NaFePO4 in sodium iron pyrophosphate active materials can be reduced, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial to improving the specific capacity of sodium iron pyrophosphate active materials.
[0156] For example, the value of y:x can be 2.8:4, 2.82:4, 2.85:4, 2.87:4, 2.9:4, 2.92:4, 2.95:4, 2.97:4 or 2.99:4, etc., and it can also be any value in the range of <3:4.
[0157] This application also provides a positive electrode active material, which includes a sodium iron pyrophosphate active material, wherein the sphericity of the sodium iron pyrophosphate active material is not less than 0.8, and the total pore volume of the sodium iron pyrophosphate active material is not greater than 0.013 cm³. 3 / g; the average pore size of the sodium iron pyrophosphate active material is no greater than 3nm.
[0158] Sodium iron pyrophosphate active materials refer to sodium iron pyrophosphate active materials that are doped or coated and modified.
[0159] Sphericity measures the degree to which particles tend towards a spherical shape. The greater the sphericity, the more spherical the particles are. Sphericity can be determined by taking electron microscope (SEM) images of sodium iron pyrophosphate active materials, importing them into IPP software for segmentation, and calculating the ratio of the particle perimeter equivalent diameter to the particle area equivalent diameter using the software's calculation function. The average sphericity is then obtained as the sphericity of the sodium iron pyrophosphate active material.
[0160] The total pore volume of sodium iron pyrophosphate active materials is a term known in the art and can be determined using instruments and methods known in the art. An exemplary test method is as follows: A certain mass of a sodium iron pyrophosphate active material sample (e.g., 1.5 g to 3.5 g) is placed in a sample tube, dried, and then degassed at 200°C for 2 hours. The sample is then placed in a Tristar II 3020 instrument analysis station for testing to obtain the total pore volume of the sodium iron pyrophosphate active material. The adsorbed gas during the test can be nitrogen, and the adsorption temperature can be 77 K (K represents Kelvin temperature).
[0161] The average aperture can be obtained by analyzing high-resolution transmission electron microscopy. Representative areas of the magnified electron image are selected, the apertures of the through holes are counted, and the average aperture of more than 10 representative areas is taken to obtain the average aperture.
[0162] This positive electrode active material, by giving the highly spherical sodium iron pyrophosphate active material particles fewer and smaller pore structures, results in a secondary battery with higher energy density.
[0163] In some embodiments of this application, the sphericity of the sodium iron pyrophosphate active material is 0.82–0.85. Higher sphericity of the sodium iron pyrophosphate active material is more conducive to the compaction density of the formed positive electrode sheet. By controlling the sphericity of the sodium iron pyrophosphate active material to 0.82–0.85, the formed positive electrode sheet can have a higher compaction density.
[0164] For example, the sphericity of sodium iron pyrophosphate active materials can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.9, etc., or any value within the range of not less than 0.8.
[0165] In some embodiments of this application, the total pore volume of the sodium iron pyrophosphate-based active material is 0.011 cm³. 3 / g~0.013cm 3 / g.
[0166] For example, the total pore volume of sodium iron pyrophosphate-based active materials can be 0.011 cm³. 3 / g, 0.0111cm 3 / g, 0.0112cm 3 / g, 0.0113cm 3 / g, 0.0114cm 3 / g, 0.0115cm 3 / g, 0.0116cm 3 / g, 0.0117cm 3 / g, 0.0118cm 3 / g, 0.0119cm 3 / g, 0.012cm 3 / g, 0.0121cm 3 / g, 0.0122cm 3 / g, 0.0123cm 3 / g, 0.0124cm 3 / g, 0.0125cm 3 / g, 0.0126cm 3 / g, 0.0127cm 3 / g, 0.0128cm 3 / g, 0.0129cm 3 / g or 0.13cm 3 / g, etc., can also be 0.011cm. 3 / g~0.013cm 3 Any value within the range / g.
[0167] In some embodiments of this application, the average pore size of the sodium iron pyrophosphate active material is 2.5 nm to 3 nm.
[0168] For example, the average pore size of sodium iron pyrophosphate active materials can be 2.5nm, 2.55nm, 2.6nm, 2.65nm, 2.7nm, 2.75nm, 2.8nm, 2.85nm, 2.9nm, 2.95nm or 3nm, etc., or it can be any value in the range of 2.5nm to 3nm.
[0169] In some embodiments of this application, the median particle size Dv50 of the sodium iron pyrophosphate active material is 0.1 μm to 0.3 μm.
[0170] The median particle size Dv50 is the particle size corresponding to 50% of the cumulative amount in the volumetric particle size distribution map. The volumetric particle size distribution map, also known as the differential particle size distribution map, is a curve plotted with particle size on the x-axis and the differential distribution of particle size at different dimensions on the y-axis. It can accurately reflect the particle size distribution characteristics of a material. A laser particle size analyzer can be used to determine the volumetric particle size distribution of the material and plot the interval particle size distribution curve. When measuring the median particle size of the positive electrode active material in the active material layer of the electrode sheet, the positive electrode active material layer can be removed, immersed in the solvent NMP, and the binder in the positive electrode active material layer can be washed out to obtain the powder material of the positive electrode active material layer. After drying the powder material, it is detected using a Mastersizer3000 laser particle size analyzer to obtain the volumetric particle size distribution map. The median particle size of the positive electrode active material can be obtained from the peaks in the volumetric particle size distribution map.
[0171] Understandably, with sphericity and average pore size remaining constant, smaller particle size results in smaller gaps between particles, which is more conducive to increasing powder compaction density.
[0172] For example, the median particle size Dv50 of sodium iron pyrophosphate active materials can be 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.2 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm or 0.3 μm, etc., or it can be any value in the range of 0.1 μm to 0.3 μm.
[0173] In some embodiments of this application, the specific surface area of the sodium iron pyrophosphate active material is 5.5 m². 2 / g~5.7m 2 / g.
[0174] Specific surface area refers to the total surface area per unit mass of a substance. Specific surface area can be measured using instruments and methods known in the art, such as nitrogen adsorption specific surface area analysis and calculated using the BET method.
[0175] For example, the specific surface area of sodium iron pyrophosphate-based active materials can be 5.5 m². 2 / g, 5.52m 2 / g, 5.54m 2 / g, 5.56m 2 / g, 5.58m 2 / g, 5.6m 2 / g, 5.62m 2 / g, 5.64m 2 / g, 5.66m 2 / g, 5.68m 2 / g, 5.7m 2 / g, etc., can also be 5.5m. 2 / g~5.7m 2 Any value within the range / g.
[0176] It should be noted that the specific surface area and volumetric particle size distribution measurements are for secondary particles, which are aggregates of primary particles.
[0177] In some embodiments of this application, the compacted density of 1T of sodium iron pyrophosphate-based active material is 1.90 g / cm³. 3 ~2.10g / cm 3 .
[0178] 1T compaction density refers to the compaction density of powder under 1T pressure. Powder compaction density can be tested using a powder compaction density meter.
[0179] For example, the compacted density of 1T of sodium iron pyrophosphate-based active materials can be 1.90 g / cm³. 3 1.95g / cm 3 2.00g / cm 3 2.05g / cm 3 Or 2.10 g / cm 3 It can also be 1.90 g / cm³. 3 ~2.10g / cm 3 Any value within the range.
[0180] In some embodiments of this application, the 3T compaction density of the sodium iron pyrophosphate-based active material is 2.10 g / cm³. 3 ~2.3g / cm 3 .
[0181] 3T compaction density refers to the compaction density of powder under 3T pressure. Powder compaction density can be tested using a powder compaction density meter.
[0182] For example, the 3T compaction density of sodium iron pyrophosphate-based active materials can be 2.10 g / cm³. 3 2.15g / cm 3 2.20g / cm 3 2.25g / cm 3 Or 2.30 g / cm 3 It can also be 2.10 g / cm³. 3 ~2.3g / cm 3 Any value within the range.
[0183] In some embodiments of this application, the active material of sodium iron pyrophosphate includes Na. x R y P m O n Wherein, 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7<m≤4.2, 14.5≤n≤15.5, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Cr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, or Pb.
[0184] The content of each element can be obtained by inductively coupled plasma atomic emission spectrometry (ICP).
[0185] It should be noted that the above limitation on x includes the molar content of Na under different charge and discharge states of the battery (typically the battery voltage is between 2-5V).
[0186] Understandably, sodium (Na) is intercalated and deintercalated during the charging and discharging process of a battery. The Na content in the positive electrode varies depending on the state of discharge. The Na content can be measured using molar content, but is not limited to this. Simultaneously, when a positive electrode material is applied to the positive electrode in a battery system, the Na content in the positive electrode material typically changes after charge-discharge cycles. In the examples of positive electrode materials listed in this application, unless otherwise specified, the Na content refers to the initial state of the material. Regarding "Na content refers to the initial state of the material," the initial state of the material refers to its state before being added to the positive electrode slurry. It is understood that new materials obtained by appropriately modifying the listed positive electrode materials are also within the scope of positive electrode materials. The aforementioned appropriate modification refers to acceptable modification methods for the positive electrode material; non-limiting examples include coating modification.
[0187] It is understandable that the molar content of R, y, and the molar content of Na are similar, so we will not elaborate on them here.
[0188] For example, Na x R y P m O n In this case, x can be 3.5, 3.55, 3.6, 3.65, 3.7, 3.75, 3.8, 3.85, 3.9, 3.95, 4, 4.05, 4.1, 4.15, 4.2, 4.25, 4.3, 4.35, 4.4, 4.45, or 4.5, or any value within the range of 3.5 to 4.5. Na x R y P m O n In this case, y can be 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, or 3.5, or any value within the range of 2.5 to 3.5. Na x R y P m O n In this case, m can be 3.7, 3.75, 3.8, 3.85, 3.9, 3.91, 3.92, 3.93, 3.94, 3.94, 3.95, 3.96, 3.97, 3.98, 3.99, 4, 4.05, 4.1, 4.15, or 4.2, etc., or any value within the range of 3.7 to 4.2. Na x R y P m O nIn this case, n can be 14.5, 14.6, 14.7, 14.8, 14.9, 15, 15.1, 15.2, 15.3, 15.4 or 15.5, etc., or any value in the range of 14.5 to 15.5.
[0189] In some embodiments of this application, y:x < 3:4. By controlling y:x < 3:4, the content of impurity phases such as NaFePO4 in sodium iron pyrophosphate active materials can be reduced, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial to improving the specific capacity of sodium iron pyrophosphate active materials.
[0190] For example, the value of y:x can be 2.8:4, 2.82:4, 2.85:4, 2.87:4, 2.9:4, 2.92:4, 2.95:4, 2.97:4 or 2.99:4, etc., and it can also be any value in the range of <3:4.
[0191] Having introduced the positive electrode active materials and structure of secondary batteries, the preparation methods of the positive electrode active materials will now be described in detail.
[0192] Figure 7 For flowcharts illustrating the preparation methods of positive electrode active materials provided in some embodiments of this application, please refer to [link / reference]. Figure 7 This application also provides a method for preparing a positive electrode active material, the method comprising:
[0193] S110. The raw materials are formulated into a mixed slurry, wherein the raw materials include a sodium source, an R source and a phosphorus source.
[0194] The solvent for the mixed slurry is selected from one or more of deionized water and organic solvents, and the organic solvent is an alcohol, such as methanol or ethanol.
[0195] The sodium source can be at least one of the following: sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, or sodium citrate. The phosphorus source includes at least one of the following: ferric pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, phosphoric acid, pyrophosphate, or ferric phosphate. The R source includes at least one of the following: a salt, oxide, or hydroxide of element R; the R source can be an iron source, which can be selected from organic iron sources such as ferric phosphate, ferric acetylacetone, ferrous oxalate, ferric acetate, ferric citrate, or ferrous citrate (organic iron sources, where elements other than iron are gaseous and disappear during the reaction, are relatively ideal iron sources, but their adverse effect on sphericity is more pronounced during the reaction). The phosphorus source includes at least one of the following: ferric pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, phosphoric acid, pyrophosphate, or ferric phosphate.
[0196] In some embodiments of this application, the raw materials further include a first carbon source. The amount of the first carbon source added is determined according to a certain proportion of the theoretically calculated finished product, specifically 1% to 5% of the theoretical finished product.
[0197] In some embodiments of this application, the first carbon source includes at least one of citric acid, oxalic acid, sucrose, fructose, pitch, glucose, ascorbic acid, graphite, carbon black, carbon nanotubes, or graphene. By adding the first carbon source, the contact between sodium iron pyrophosphate and external environment elements such as water during the preparation and use of the active material can be reduced, thereby reducing the generation of residual alkali during preparation and use.
[0198] In some embodiments of this application, the ratio of iron to sodium in the raw materials is less than 3:4. By controlling the ratio of iron to sodium in the raw materials to be less than 3:4, the content of impurities such as NaFePO4 in the generated sodium iron pyrophosphate active material can be reduced, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial to improving the specific capacity of the sodium iron pyrophosphate active material.
[0199] By controlling the ratio of iron to sodium to be less than 3:4, the content of impurities such as NaFePO4 in sodium iron pyrophosphate active materials can be reduced, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial to improving the specific capacity of sodium iron pyrophosphate active materials.
[0200] For example, the ratio of iron to sodium can be 2.8:4, 2.82:4, 2.85:4, 2.87:4, 2.9:4, 2.92:4, 2.95:4, 2.97:4, or 2.99:4, etc., or any value within the range of less than 3:4.
[0201] S120. The mixed slurry is granulated to obtain mixed particles.
[0202] Before granulation, the mixed slurry can be sand-milled to a certain particle size. Specifically, the grinding media (zirconia balls) should have a diameter of 0.2–0.6 mm, and the median particle size (Dv50) of the solid components in the mixed slurry should be 0.1–0.3 μm. A dispersant should be added during sand-milling, with the amount of dispersant being 0.1%–2% of the total solid mass. The dispersant includes, but is not limited to, one or more of PEG-2000, PEG-6000, polyacrylates, and lignin dispersants to ensure the uniformity of the slurry. At this time, the sodium source and the first carbon source, which are soluble in deionized water, are uniformly coated on the surface of the secondary particles of the very small, water-insoluble raw materials. After the slurry is mixed evenly and the particle size meets the standard, it is demagnetized and dried. The granulation method can be spray drying, with an inlet temperature of 250–300℃ and an outlet temperature of 110–150℃, ensuring a solvent content of 0%–3%. The microstructure of the sprayed material is spherical.
[0203] S130. The mixed particles are sintered once to obtain an intermediate, wherein the temperature of the first sintering is greater than 370°C.
[0204] Because the aforementioned sodium source and first carbon source are soluble in deionized water, the material morphology after sintering is microscopically bonded together (in the form of secondary particles). At the same time, at this temperature, the raw material decomposes and produces gas, and the crystal water in it produces gas. The gas inside and between the secondary particles breaks through the carbonization layer and is discharged along certain gaps, forming a porous structure from the particle surface to the inside, causing severe damage to the surface of the sprayed material and a significant reduction in sphericity.
[0205] In some embodiments of this application, the temperature of the first sintering is 420℃~450℃; the time of the first sintering is 5h~15h. Higher first sintering temperatures and longer times facilitate the release of lattice water in the raw materials and gases generated during the formation of sodium iron pyrophosphate-based active materials, thereby reducing the possibility of porous structures caused by gases during secondary sintering. Lower first sintering temperatures and shorter times reduce energy consumption, thus contributing to cost control. By controlling the first sintering temperature to 420℃~450℃ and the time to 5h~15h, it is possible to balance the need for fewer and smaller pore structures in the sodium iron pyrophosphate-based active materials with cost control.
[0206] For example, the sintering temperature can be 375℃, 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, or 450℃, or any value within the range of 320℃ to 450℃. The sintering time can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, or 15h, or any value within the range of 5h to 15h.
[0207] S140. The intermediate material is subjected to wet shaping to obtain a primary slurry.
[0208] In some embodiments of this application, the solvent used for wet forming is an organic solvent. Specifically, the organic solvent can be ketones, esters, sulfones, or alcohols. Sodium iron pyrophosphate active materials are insoluble in organic solvents; in other words, sodium ions will not be released from the surface of the sodium iron pyrophosphate active material where it comes into contact with the solvent. This reduces the possibility of impurity phases such as NaFePO4 being generated in the sodium iron pyrophosphate active material, thereby increasing the content of Na4R3(PO4)2P2O7, which is beneficial for improving the specific capacity of the sodium iron pyrophosphate active material.
[0209] In some embodiments of this application, the organic solvent includes alcohol solvents. Specifically, alcohol solvents can be methanol, ethanol, etc. By using alcohol solvents as solvents in wet forming, alcohol solvents typically have lower boiling points, which can reduce the temperature of subsequent spray drying granulation, thereby reducing energy consumption and contributing to cost control.
[0210] In some embodiments of this application, the initial slurry may further include a second carbon source. The amount of the second carbon source added may be 1% to 10% of the mass of the solid components in the wet-forming slurry.
[0211] In some embodiments of this application, the second carbon source includes at least one of citric acid, oxalic acid, sucrose, fructose, pitch, glucose, ascorbic acid, graphite, carbon black, carbon nanotubes, or graphene. By adding a second carbon source, the contact between sodium iron pyrophosphate and external environment elements such as water during the preparation and use of the active material can be reduced, thereby reducing the generation of residual alkali during preparation and use.
[0212] In some embodiments of this application, the difference between the median particle size Dv50 of the solid phase in the initial slurry and the median particle size Dv50 of the solid phase in the mixed slurry is no greater than 0.2 μm. By controlling the difference between the median particle size Dv50 of the solid phase in the initial slurry and the median particle size Dv50 of the solid phase in the mixed slurry to be no greater than 0.2 μm, the pore structure in the intermediate is opened as completely as possible, which is beneficial to reduce and minimize the pore structure of the final sodium iron pyrophosphate-based active material.
[0213] Before wet shaping, the intermediate material can be crushed. The crushing method can be one of jaw crusher, roller crusher, air jet mill, or mechanical crusher.
[0214] The intermediate material after crushing has a small particle size and forms porous particles after sintering, making it easier to grind to a smaller particle size. Therefore, the solid content of the slurry in wet forming can be increased to 40% to 50%, and the particle size can be ground to 0.1μm to 0.3μm in a short time of 2h to 4h, which can effectively improve efficiency.
[0215] The wet-processed slurry may include a grinding aid, the amount of which may be 0.1% to 3% of the mass of the solid components in the wet-processed slurry.
[0216] S150. The initial slurry is spray-dried and granulated to obtain initial granules.
[0217] When the solvent used for wet forming is an alcohol solvent, in some embodiments of this application, the inlet air temperature of spray drying granulation is 180°C to 250°C, and the outlet temperature of spray drying granulation is 85°C to 95°C.
[0218] It is understandable that when the solvent used in wet forming is not an alcohol solvent, the temperature of spray drying granulation can be adjusted according to the characteristics of the solvent.
[0219] S160. The initial product particles are subjected to secondary sintering to obtain sodium iron pyrophosphate-based active materials.
[0220] In some embodiments of this application, the temperature of the secondary sintering can be 500℃~600℃, and the time of the secondary sintering can be 24h~34h.
[0221] Higher secondary sintering temperatures and longer times promote more complete reaction of raw materials into sodium iron pyrophosphate-based active materials. Conversely, lower secondary sintering temperatures and shorter times reduce energy consumption, thus improving cost control. By controlling the secondary sintering temperature to 500℃–600℃ and the time to 24h–34h, both the yield and cost of sodium iron pyrophosphate-based active materials can be balanced.
[0222] Because the gas is already released during the first sintering stage, there is no significant gas generation during the sintering process. This results in the sintered sodium iron pyrophosphate active material maintaining a high degree of sphericity and retaining a small amount of voids between secondary particles. After being removed from the furnace, it is pulverized, sieved, and demagnetized to obtain a high-density sodium iron pyrophosphate active material with extremely high sphericity.
[0223] This method employs a combination of single-stage sintering, wet shaping, and spray drying granulation. Single-stage sintering allows for the pre-release of lattice water and gases generated during the formation of sodium iron pyrophosphate-based active materials from the raw materials. Wet shaping then eliminates the porosity caused by the release of lattice water and gases during single-stage sintering. Finally, spray drying granulation ensures that the prepared sodium iron pyrophosphate-based active materials have high sphericity. Ultimately, the resulting sodium iron pyrophosphate-based active material particles exhibit high sphericity and fewer and smaller pores, leading to a high energy density in the formed secondary battery.
[0224] After obtaining the aforementioned sodium iron pyrophosphate active material, it can be formulated into a positive electrode active slurry and coated onto a positive electrode current collector to obtain a positive electrode sheet. Then, the positive electrode sheet is assembled into a secondary battery. The specific process can be as follows: the positive electrode active material, conductive agent and binder are mixed and then mixed with a solvent to prepare a positive electrode active slurry. The positive electrode active slurry is coated onto the positive electrode current collector 2311 to obtain a positive electrode sheet 231. After preparing the positive electrode sheet 231, the positive electrode sheet 231, the separator, the negative electrode sheet, the separator, and so on are stacked in sequence to form a stacked electrode assembly 23. Then, the electrode assembly 23 is placed in the housing and an electrolyte is injected to form a secondary battery.
[0225] Figure 8 This is a flowchart illustrating the fabrication process of a secondary battery provided in some embodiments of this application, such as... Figure 8 As shown, the specific process for preparing a secondary battery is as follows:
[0226] S210, Preparation of positive electrode active slurry: The positive electrode active material, binder, and conductive agent are dispersed in a solvent to form a positive electrode active slurry. The positive electrode active material used is the one provided above, namely, sodium iron pyrophosphate-based active material. Optionally, a small amount of other positive electrode active materials may be added.
[0227] The binder can be one or more of styrene-butadiene rubber, waterborne acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and polyvinyl butyral. The conductive agent can be at least one of conductive carbon black, carbon fiber, carbon nanotubes, Ketjen black, graphene, or acetylene black. The solvent can be one or more of dimethyl glutarate and N-methylpyrrolidone. Leveling agents, dispersants, etc., can also be added to the positive electrode active slurry.
[0228] S220, Preparation of positive electrode active material layer 2312: The positive electrode active slurry is coated on the surface of the positive electrode current collector 2311 and then dried to form the positive electrode active material layer 2312. During coating, it can be applied to one or both surfaces of the positive electrode current collector 2311 as needed.
[0229] The coating method can be: scraping, roller coating, slot coating, etc., and this application does not limit it.
[0230] The positive electrode current collector 2311 can be a metal foil or a composite current collector. For example, aluminum foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0231] S230, roll-press the positive electrode active material layer 2312 to obtain the positive electrode sheet 231.
[0232] S240, positive electrode 231, separator, negative electrode, separator, and so on are stacked in sequence to form a stacked electrode assembly 23.
[0233] S250, the stacked electrode assembly 23 is assembled into a battery cell 20. This battery cell 20 can be used to prepare a secondary battery 100 and provide electrical energy to an electrical device.
[0234] The following examples will describe one or more embodiments in more detail. Of course, these examples do not limit the scope of the one or more embodiments.
[0235] Examples and Comparative Examples
[0236] Preparation of positive electrode active materials
[0237] Sodium dihydrogen phosphate (sodium source), ferrous oxalate (iron source), and phosphoric acid (phosphoric source) were dissolved in deionized water at a specific molar ratio and stirred continuously at room temperature for 30 minutes to obtain an initial mixed slurry. Oxalic acid (the first carbon source) was dissolved in deionized water and mixed to obtain a carbon solution. This carbon solution was then mixed with the initial mixed solution and stirred to obtain a mixed slurry. The mixed slurry was spray-dried at an inlet air temperature of 220°C and an outlet air temperature of 109°C to obtain mixed particles. The mixed particles were then subjected to a first sintering process for 10 hours to obtain an intermediate. This intermediate was then wet-shaped at 2000 rpm for 2 hours to obtain a preliminary slurry. This preliminary slurry was then spray-dried to obtain preliminary particles. Finally, a second sintering process was performed in a N2 atmosphere, with the temperature increased to 520°C at a rate of 2°C and held for 24 hours. The sintered product was then subjected to air jet milling and sieved to obtain a uniformly sized positive electrode active material.
[0238] Preparation of the positive electrode sheet
[0239] 2.5 wt% of the binder polyvinylidene fluoride was fully dissolved in the solvent N-methylpyrrolidone. 2.0 wt% of super p and 1.0 wt% of CNT were added as conductive agents, and 94.5 wt% of the above-mentioned positive electrode active material were mixed to form a uniformly dispersed slurry. The slurry was uniformly coated onto the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and slitting, the positive electrode sheet was obtained.
[0240] Preparation of the negative electrode sheet
[0241] Sodium metal sheet is used as the negative electrode.
[0242] Preparation of Electrolyte
[0243] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), the organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) are mixed evenly in a volume ratio of 1 / 1 / 1. 1 mol / L NaPF6 sodium salt is added and dispersed evenly. Then, 5% fluoroethylene carbonate is dissolved in the above organic solvent and stirred evenly to obtain the electrolyte.
[0244]
Isolation Film
[0245] Polyethylene film is used as the separation membrane.
[0246] [Preparation of button cells]
[0247] The prepared positive electrode, negative electrode, separator and electrolyte are assembled into CR2430 button cell in an argon-protected glove box.
[0248] The results of main parameter control and intermediate-related parameter detection during the preparation process of Examples 1 to 11 and Comparative Examples 1 to 3 are shown in the table below:
[0249]
[0250] In the table, x and y refer to the molar ratio of sodium and iron in the raw materials, respectively.
[0251] The ' / ' symbol indicates that the operation was not performed or that the value does not exist.
[0252] Carbon content was determined using a carbon-sulfur analyzer.
[0253] The specific surface area test method is as follows: Using a specific surface area and porosity tester, accurately weighed pretreated sample is placed in the sample tube. First, the sample is degassed by vacuuming, and then the entire system is brought to the required vacuum level. The sample tube is then immersed in a liquid nitrogen bath and filled with nitrogen gas. The adsorbent adsorbs gas, causing a pressure drop. After adsorption equilibrium is reached, the equilibrium pressure of the gas is measured, and the adsorption amount can be calculated based on the pressure change of the system before and after adsorption. The amount of adsorbate gas is gradually increased into the system to change the pressure, and the above operation is repeated to test the adsorption-desorption isotherms. The specific surface area of the sample is then calculated using a theoretical model.
[0254] The method for testing total pore volume is as follows: A certain mass of the sample to be tested (e.g., 1.5 g to 3.5 g) is placed into a sample tube, dried, and then degassed at 200 °C for 2 h. The sample is then placed in a Tristar II 3020 instrument analysis station for testing to obtain the total pore volume of the sample. The adsorbed gas during the test can be nitrogen, and the adsorption temperature can be 77 K (K represents Kelvin temperature).
[0255] The average aperture test method is as follows: High-resolution transmission electron microscopy is used for analysis. Representative areas of the electron magnification image are selected, and the aperture of the through holes is counted. The average aperture is obtained by taking the average of the apertures of more than 10 representative areas.
[0256] The test method for median particle size Dv50 is as follows: A laser particle size analyzer of model Mastersizer3000 is used to detect the cumulative distribution map of volumetric particle size. The median particle size can be obtained from the peaks in the cumulative distribution map of volumetric particle size.
[0257] The SEM results of the intermediates in Examples 1 to 2 and Comparative Examples 1 to 3 are as follows: Figures 9 to 13 As shown.
[0258] From the table above and Figures 9 to 13It was found that during pre-sintering at 340℃, 360℃, and 370℃, the burn-off rate gradually increased from 15% to 20%, while the carbon content gradually decreased from 1.3% to 1.2%. This suggests that the organic carbon source in the raw material was completely carbonized at this point, and the oxalate gradually began to decompose and participate in the synthesis of sodium iron pyrophosphate-based active materials. At this stage, SEM images showed the agglomeration of primary particles and secondary particles of the intermediate material, with pores generated within the primary particles and a small number of pores on the surface, and the average pore size increasing to 1.6 nm. When the temperature reached 420℃, SEM images showed a large distribution of large-diameter pores on the surface and inside the intermediate material, with a carbon content of 1.28%. At this temperature, the oxalate produced a large amount of gas during the chemical reaction, and the burn-off rate reached 22%. At this point, a porous sodium iron pyrophosphate-based active material had been formed, with a total pore volume of 0.018 / (cm³). 3 / g), with an average pore size increasing to 12.3 nm; when the temperature continued to rise to 520℃, SEM images showed a large distribution of large-diameter pores on both the surface and inside of the intermediate material. Compared with sintering at other temperatures, the surface morphology of the material exhibited extremely poor sphericity and severe fragmentation; with a carbon content of 1.25%, the iron phosphate produced a large amount of gas during the chemical reaction at this temperature, resulting in a complete reaction and a burn-off rate of 25%. At this point, a porous sodium iron pyrophosphate-based active material had been formed, with a total pore volume of 0.22 / (cm³). 3 The average pore size increased to 16.2 nm. Therefore, it is determined that the raw material can only achieve a greater amount of gas production when the temperature is not less than 370℃, which is beneficial to the control of the sphericity and pore structure of the subsequently prepared sodium ferric pyrophosphate.
[0259] The positive electrode active materials provided in each embodiment and comparative example were tested, and the tests specifically included:
[0260] Carbon content was determined using a carbon-sulfur analyzer.
[0261] The specific surface area test method is as follows: Using a specific surface area and porosity tester, accurately weighed pretreated sample is placed in the sample tube. First, the sample is degassed by vacuuming, and then the entire system is brought to the required vacuum level. The sample tube is then immersed in a liquid nitrogen bath and filled with nitrogen gas. The adsorbent adsorbs gas, causing a pressure drop. After adsorption equilibrium is reached, the equilibrium pressure of the gas is measured, and the adsorption amount can be calculated based on the pressure change of the system before and after adsorption. The amount of adsorbate gas is gradually increased into the system to change the pressure, and the above operation is repeated to test the adsorption-desorption isotherms. The specific surface area of the sample is then calculated using a theoretical model.
[0262] The method for testing total pore volume is as follows: A certain mass of the sample to be tested (e.g., 1.5 g to 3.5 g) is placed into a sample tube, dried, and then degassed at 200 °C for 2 h. The sample is then placed in a Tristar II 3020 instrument analysis station for testing to obtain the total pore volume of the sample. The adsorbed gas during the test can be nitrogen, and the adsorption temperature can be 77 K (K represents Kelvin temperature).
[0263] The average aperture test method is as follows: High-resolution transmission electron microscopy is used for analysis. Representative areas of the electron magnification image are selected, and the aperture of the through holes is counted. The average aperture is obtained by taking the average of the apertures of more than 10 representative areas.
[0264] Testing of 1T compaction density and 3T compaction density: The tests were conducted using a powder compaction density meter.
[0265] The test results are shown in the table below:
[0266]
[0267] It should be noted that since the sodium iron pyrophosphate of Comparative Examples 1 to 5 did not appear to be spherical in the SEM images, their sphericity was not measured.
[0268] As can be seen from the table above, the sodium iron pyrophosphate active material prepared by using the method provided in the embodiments of this application, through the combined use of one-time sintering, wet shaping and spray drying granulation, has high sphericity and fewer and smaller pore structures.
[0269] By comparing the data from Comparative Examples 1 to 3 and Examples 1 to 2, it can be seen that as the pre-sintering temperature gradually increases, the sphericity of sodium iron pyrophosphate gradually increases. When the pre-sintering temperature is controlled to be not less than 420°C, the sphericity of sodium iron pyrophosphate is above 0.83.
[0270] By comparing the data from Examples 1 and 3 to 4, it can be seen that as the difference between the median particle size Dv50 of the solid phase in the primary slurry and the median particle size Dv50 of the solid phase in the mixed slurry gradually decreases, the pore structure of sodium iron pyrophosphate gradually decreases. By controlling the difference between the median particle size Dv50 of the solid phase in the primary slurry and the median particle size Dv50 of the solid phase in the mixed slurry to be below 0.2 μm, the average pore size of sodium iron pyrophosphate is below 0.132 μm.
[0271] The secondary batteries provided in each embodiment and comparative example were tested, and the tests specifically included:
[0272] Electrode compaction density test: This test measures the mass (g / cm³) of the positive electrode active material layer per unit area on one side. 2The density of the positive electrode active material layer (PD) is determined by the thickness (cm) of the positive electrode active material layer on one side (number of sampling points > 14). Specifically, the compaction density PD of the positive electrode active material layer is equal to the mass of the positive electrode active material layer on one side per unit area (g / cm³). 2 ) / Thickness of the positive electrode active material layer (cm).
[0273] Energy density testing: At 25℃, the prepared battery was charged to 3.75V with a constant current of 1C, then charged at a constant voltage of 3.75V until the current dropped to 0.05C, and finally discharged to 1.5V with a constant current of 1C to obtain the discharge capacity (Cd1). The energy density was then obtained using the formula: Energy density = Discharge capacity * Discharge plateau voltage / Battery volume. The discharge plateau voltage is the potential at which the electrochemical reaction reaches equilibrium, and is generally automatically extracted by testing equipment. The battery volume was determined using the water displacement method, where the battery was placed in pure water, and the volume of water displaced was removed. The battery capacity was tested using a battery tester.
[0274] The test results are shown in the table below:
[0275]
[0276] As can be seen from the table above, the secondary battery prepared using the method provided in the embodiments of this application with sodium iron pyrophosphate as the positive electrode active material can be prepared by using a larger cold pressing pressure, so that the positive electrode sheet has a higher compaction density, thereby enabling the secondary battery to have a higher energy density.
[0277] By comparing the data from Comparative Examples 1 to 3 and Examples 1 to 2, it can be seen that as the pre-sintering temperature gradually increases, the energy density of the secondary battery generally shows a gradual increasing trend. When the pre-sintering temperature is controlled to be no less than 420°C, the energy density of the secondary battery is above 276Wh / L.
[0278] Comparison of data from Examples 1 and 3 to 4 shows that as the difference between the median particle size Dv50 of the solid phase in the initial slurry and the median particle size Dv50 of the solid phase in the mixed slurry gradually decreases, the overall energy density of the secondary battery shows a gradually decreasing trend. By controlling the difference between the median particle size Dv50 of the solid phase in the initial slurry and the median particle size Dv50 of the solid phase in the mixed slurry to be below 0.2 μm, the energy density of the secondary battery is above 276 Wh / L.
[0279] The above are merely specific embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A secondary battery, characterized in that, The secondary battery includes a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least a portion of the surface of the positive current collector. The positive active material layer includes a positive active material, which is a sodium iron pyrophosphate-based active material. The sphericity of the sodium iron pyrophosphate-based active material is not less than 0.8, and the total pore volume of the sodium iron pyrophosphate-based active material is not greater than 0.013 cm³. 3 / g.
2. The secondary battery according to claim 1, characterized in that, The average pore size of the sodium iron pyrophosphate active material is no greater than 3 nm.
3. The secondary battery according to any one of claims 1 to 2, characterized in that, The sphericity of the sodium iron pyrophosphate active material is 0.82–0.85; and / or The total pore volume of the sodium iron pyrophosphate-based active material is 0.011 cm³. 3 / g~0.013cm 3 / g; and / or The average pore size of the sodium iron pyrophosphate active material is 2.5 nm to 3 nm; and / or The median particle size Dv50 of the sodium iron pyrophosphate active material is 0.1 μm to 0.3 μm; and / or The specific surface area of the sodium iron pyrophosphate active material is 5.5 m². 2 / g~5.7m 2 / g; and / or The compacted density of the sodium iron pyrophosphate active material is 1.90 g / cm³. 3 ~2.10g / cm 3 ; and / or The 3T compaction density of the sodium iron pyrophosphate active material is 2.10 g / cm³. 3 ~2.3g / cm 3 .
4. The secondary battery according to any one of claims 1 to 3, characterized in that, The compaction density of the positive electrode sheet is 2.1 g / cm³. 3 ~2.2g / cm 3 .
5. An electrical device, characterized in that, The electrical device includes the secondary battery as described in any one of claims 1 to 4.
6. A positive electrode active material, characterized in that, The positive electrode active material includes a sodium iron pyrophosphate active material, wherein the sphericity of the sodium iron pyrophosphate active material is not less than 0.8, and the total pore volume of the sodium iron pyrophosphate active material is not greater than 0.013 cm³. 3 / g.
7. A method for preparing a positive electrode active material, characterized in that, The method includes: The raw materials are formulated into a mixed slurry, wherein the raw materials include a sodium source, an iron source, and a phosphorus source; The mixed slurry is granulated to obtain mixed particles; The mixed particles are sintered once to obtain an intermediate, and the temperature of the first sintering is greater than 370°C. The intermediate material is subjected to wet shaping to obtain a primary slurry. The initial slurry is spray-dried and granulated to obtain initial granules; The initial particles are sintered to obtain the positive electrode active material.
8. The method for preparing the positive electrode active material according to claim 7, characterized in that, The temperature of the first sintering is 420℃~450℃; and / or The sintering time for the first sintering is 5h to 15h; and / or The secondary sintering temperature is 500℃~600℃; and / or The secondary sintering time is 24h to 34h; and / or The difference between the median particle size Dv50 of the solid phase in the primary slurry and the median particle size Dv50 of the solid phase in the mixed slurry is not greater than 0.2 μm; and / or The solvent used in the wet forming process is an organic solvent.
9. The method for preparing the positive electrode active material according to claim 8, characterized in that, The organic solvent includes alcohol solvents; and / or The inlet air temperature of the spray drying granulation is 180℃~250℃, and the outlet air temperature of the spray drying granulation is 85℃~95℃.
10. The method for preparing the positive electrode active material according to any one of claims 7 to 9, characterized in that, The iron source includes at least one of ferric phosphate, ferric acetylacetone, ferrous oxalate, ferric acetate, ferric citrate, or ferrous citrate.